Landowska on Music - Landowska, Wanda 1879-1959; Restout, Denise 1915-2004; Hawkins, Robert (London Secker & Warburg, 1965)
Acknowledged by many as the high priestess of the harpsichord, Landowska long reigned as the godmother of 20th-century harpsichordists, through the direct influence she held over them, the power of her personality, and her active, lifelong career that symbolized the resurrection of the harpsichord.
Part One: Musique ancienne -- Part Two: On the Interpretation of Johann Sebastian Bach's Keyboard Works -- George Frederic Handel -- Domenico Scarlatti -- A Glorious Trinity -- French Music of the Past -- Polish Music of the Past -- English Music of the Past -- The Gallant Style -- Part Three: Thoughts on Modern Music -- Is Music of the Past UNnderstood Today? -- The Making of an Interpreter -- Reflections on Some Problems of Interpretation -- The Mysteries of Interpretation
Denise Restout was entrusted with Landowska's estate in 1959.
Landowska's Discography p. 411; Index, p. 425
"To Roberto. All good wishes, may this book surprise you in the years to come. Mom & Dad"
Collected, edited, and translated by Denise Restout. Assisted by Robert Hawkins
Keywords: 20th Century (1901-2000); Early music; Historically informed performance; Instrumentalist; Female; Harpsichord; Paris (France)